Specific Features of Military Students’ Lexical Culture Development in the Universities of EMERCOM of Russia (Proceedings of Southern Federal University. Philology, 2019)
Elena V. Lopanova (Khimki, Russian Federation)This article is devoted to the identification of the essence, content and specific features to develop the military students’ lexical culture from the universities of EMERCOM of Russia. It is emphasized that the lexical culture of the specialists of EMERCOM of Russia is based on the observance of lexical norms and the appropriateness of using lexical means.Key words: lexical culture development, word usage, professional lexis, military students of the universities of EMERCOM of Russia.DOI 10.23683/1995-0640-2019-3-202-207